Praise Israel for wisdom and instruction : essays on Ben Sira and wisdom, the Letter of Aristeas and the Septuagint - Wright, Benjamin G., III (Supplements to the Journal for the study of Judaism ;, 2008)
Features fifteen articles that focus on three interrelated themes in the study of Early Judaism. This work explores how specific wisdom and apocalyptic texts relate. It also focuses on how traditional material was shaped and framed in order to ensure its successful transmission to subsequent generations.